Assessing turbine passage effects on internal fish injury and delayed mortality using X-ray imaging - Mueller,Melanie; Sternecker,Katharina; Milz,Stefan; Geist,Juergen (PeerJ, 2020)
Knowledge on the extent and mechanisms of fish damage caused by hydropower facilities is important for the conservation of fish populations. Herein, we assessed the effects of hydropower turbine passage on internal fish injuries using X-ray technology. A total of 902 specimens from seven native European fish species were screened for 36 types of internal injuries and 86 external injuries evaluated with a previously published protocol. The applied systematic visual evaluation of X-ray images successfully detected skeletal injuries, swim bladder anomalies, emphysema, free intraperitoneal gas and hemorrhages. Injuries related to handling and to impacts of different parts of the hydropower structure could be clearly distinguished applying multivariate statistics and the data often explained delayed mortality within 96 h after turbine passage. The internal injuries could clearly be assigned to specific physical impacts resulting from turbine passage such as swim bladder rupture due to abrupt pressure change or fractures of skeletal parts due to blade-strike, fluid shear or severe turbulence. Generally, internal injuries were rarely depicted by external evaluation. For example, 29% of individuals with vertebral fractures did not present externally visible signs of severe injury. A combination of the external and internal injury evaluation allows quantifying and comparing fish injuries across sites, and can help to identify the technologies and operational procedures which minimize harm to fish in the context of assessing hydropower-related fish injuries as well as in assessing fish welfare.
Keywords: Animal welfare; Fish conservation; Fish mortality; Fish passage; Fish radiographic anatomy; Fish health